Analisis Sentimen Kepuasan Pengguna Lintas Rel Terpadu (LRT) menggunakan Metode Support Vector Machine - Rangga Febri Kasih; Rendra Gustriansyah; Zaid Romegar Mair (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
This study aims to analyze public sentiment toward the Palembang LRT service by utilizing user reviews available on the Google Maps platform. Sentiment analysis was conducted to understand public perceptions of service quality, which can serve as a basis for decision-making in improving public transportation services. The method employed in this research is the Support Vector Machine (SVM) algorithm combined with Term Frequency-Inverse Document Frequency (TF-IDF) for word weighting, which classifies reviews into two sentiment categories: positive and negative. A total of 500 reviews were randomly selected as the dataset and processed through a text preprocessing stage, including data cleaning, tokenization, and stopword removal to enhance data quality. The SVM model was then evaluated using an 80:20 split for training and testing, achieving an accuracy of 91%, which indicates excellent performance in identifying sentiment patterns in the Indonesian language. The findings of this study confirm that SVM-based approaches are effective and reliable for sentiment analysis in the context of public transportation. These results provide practical contributions for Palembang LRT management, as insights into public sentiment can be used as a strategic reference for decision-making, reputation management, and improving service quality based on user needs. Future research is recommended to expand the dataset, include neutral sentiment categories, and compare SVM performance with other machine learning algorithms to achieve more comprehensive and robust results.